Quantitative Histological Studies on the Parenchyma of Adrenal Glands of Marwari Sheep (Ovis aries) - Nama, K. G.; Mathur, Rakesh; Dangi, Ashok (Indian Journal of Veterinary Anatomy, 2016)
Adrenal glands collected from 36 adult male Marwari sheep were examined microscopically.The sections revealed that the cortex constituted the major component (56.88%) followed by the medulla (40.63%) and the capsule (2.49%). In the cortical zones, the zona glomerulosa cells were the smallest (diameter 13.91Î¼m) with an intermediate sized nucleus (diameter 6.03 Î¼m); whereas the fasciculata had the largest cells (diameter 18.57Î¼m) with relatively larger nucleus (6.8 Î¼m). The zona reticularis showed intermediate size cells (15.47Î¼m diameter) but with the smallest nucleus (5.78 Î¼m). The average nucleo-cytoplasmic ratio was 2.3, 2.73 and 2.67 in glomerulosa, fasciculata and reticularis, respectively. The medullary cells were however much larger and were more plumpy type with an average diameter of 36.15Î¼m, a nuclear diameter of 8.74 Î¼m and a nucleo-cytoplasmic ratio of 4.17. Thus indicating that the highest metabolic turn over was in the cells of medulla followed by that in the fasciculata, glomerulosa and reticularis in that order.